Evaluation of Growth and Yield Characters of Garden Pea Genotypes at Dailekh, Mid-Western Nepal - Luitel, Binod Prasad; Pun, Tul Bahadur; Bhandari, Bishnu Bahadur (Nepalese Horticulture, 2021)
Knowledge of phenotypic variation among the germplasm is important for the breeding program of garden pea. This study was conducted to evaluate the growth and yield traits of garden pea genotypes and to identify high yielding, and powdery mildew resistant genotype at Horticulture Research Station (HRS), Dailekh, Mid-western Nepal. Eleven garden pea genotypes were evaluated in the main production season (2018-2019) and compared with 'Sikkim Local' as standard variety, and the experiment was laid out in randomized complete block design with three replications. The analysis of variance revealed that genotypes had significant variation for all the traits studied except few insignificant traits. Significantly higher number of green pod/plant, green pod yield/plant, seed number/pod and seed yield/plant were recorded in genotypes DGP-12-18-2 and DGP-12-18-1 as compared with other studied genotypes. Genotype DGP-12-18-2, and DGP-12-18-1 exhibited resistant (2) to powdery mildew disease and these genotypes showed 45.8% and 16.6% yield advantage over the standard check 'Sikkim Local' variety. Therefore, genotypes DGP-12-18-2 and DGP-12-18-1 can be recommended to produce for fresh green pod and seed yield at on-farm condition of Mid-Western Nepal.